The effect of positive psychology intervention on psychological well-being of drugs inmates - Tabatabaee, Seyed Mosa; Albooyeh, Gohar; Safari, Hadi; Rajabppor, Mojtaba (International Journal of Applied Behavioral Sciences, 2016)
Introduction: Positive psychology is a new branch of psychology. The focus of this field is on personal growth; and rather than treating illness, it utilizes scientific methods to aid the achievement of a satisfactory life. This study aimed to investigate the effectiveness of positive psychology intervention on psychological well-being of drugs inmates. Methods: The subjects were 30 male drugs inmates in Semnan prison. They were selected through random sampling and randomly assigned to experimental 15 and control groups 15. All participants answered to psychological well-being scale before and after intervention. Experimental group received positive psychology intervention during 12 sessions while control group received no therapy. Data was analyzed using multiple analysis of variance. Results: The statistical analysis showed the mean psychological well-being of the experimental group was meaningfully higher than the mean of psychological well-being of the control group. Conclusion: positive psychology intervention by focusing on personal growth, rather than treating mental illness can improve psychological wellbeing of drug inmates. Declaration Interest: None